Badanie sprawności narracyjnej na podstawie tekstu ucznia z trudnościami w czytaniu i pisaniu (Conversatoria Linguistica, 2019)
The article is an attempt to analyze a fairy tale (magical) written by a student withdifficulties in reading and writing. The work is a fragment of a wider study of narrative texts ofpeople with linguistic disorders resulting mainly from the insufficient language and/or communicationalskills (Grabias 2012). The main question stated in this article concerns the correlationbetween the language skills and the narrative efficiency, between the high and low skills inboth areas.The analysis of the language skills in the student’s text shows that the level of the linguisticcompetence is insufficient. The student almost does not use punctuation, he makes numerousspelling mistakes and uses stereotypical language constructions. Nevertheless, the student’stext, despite the abovementioned linguistic defects, is coherent, and proves the ability to usesuperstructures in the understanding of Labov. It also proves the student’s ability to build thesuperior sense of the story through the appropriate functionalization of the particular motifs.In view of the above, it seems to me that in the case of a significant difference between the languageand narrative skills exposed on a larger number of the research samples, it would be possibleto hypothesize on the various sources of the mechanisms of the abovementioned abilities.